Fatores críticos de sucesso na implantação de um sistema de gestão da manutenção de ativos na indústria têxtil - Lima, Hellany Cybelle Araújo de (2020)
The textile sector in Brazil is represented as the second largest employer in the transformation industry (ABIT, 2017), being of fundamental importance that its products reach the final consumer with a better time, quality and quantity outlined. For this to happen, it is important that the production and maintenance function are in harmony with the company's structural strategy, facing challenges in the implementation of good asset management practices. The challenges of modern society in terms of physical asset management are enormous, the maintenance function and asset management play an important role in organizations through the creation of value, because by arranging asset management with top management, maximum profitability is extracted from them, ensuring that safety and risk conditions are ensured. The study and application of a maintenance management system is essential to optimize the management of a company's assets, using an investigative scope in the challenges of implementing a strategic maintenance planning. Analyzing this scenario, the work presented in this dissertation aimed to identify the critical factors for the implementation of Asset Management at the foundation of the textile industrial chain, specifically in the clothing sector, through the identification of demand. The requirements of the ABNT NBR ISO 55000 standard for asset management that contribute to an excellent management of the assets of a cofection will also be addressed. The case study methodology was used to investigate the current stage of the company's maintenance system and to identify the challenges in implementing maintenance asset management, through the 13 critical success factors in maintenance management found in the literature.